(untitled) (Biological Sciences - PJSIR, 2022)
The corrosion behaviour of pure tin in deaerated solutions of oxalic, tartaric and citric acids in the presence and absence of NO;, NO and cr anions were studied by means of potential-time measurements, corrosion rate and galvanostatic technique at thepHrange 2.5 - 6.5 forO.1Mof the three tested acids. AtpH4.5 there is amaximum negative potential for oxalic acid and at pH 5.5 for tartaric and citric acids. From pH 2.5 to 4.5, the corrosion mechanism is anodically controlled by the reaction of Sn+2ion with the anion ofthe tested acids. AtpH 5.5 the corrosion of tin is reduced which may be due to the formation of a film on the tin electrode resulting from the hydrolysis of tin complex species., The potential of the tin electrode in the three tested acid solutions tends to be shifted to the less negative values in the presen e ofaddirives NO;, N03 and CI anions at pH 4.5.